Video consultation in general practice: a scoping review on use, experiences, and clinical decisions - Magnus Repstad Wanderås; Eirik Abildsnes; Elin Thygesen; Santiago Gil Martinez (BMC, 2023)
Abstract Background The coronavirus disease 2019 pandemic forced healthcare workers to use alternative consultation approaches. In general practice, the use of video consultations (VCs) increased manyfold as countries were locked down. This scoping review aimed to summarize scientific knowledge concerning the use of VC in general practice and focused on (1) the utilization of VC in general practice, (2) the experiences of the users of VC in general practice, and (3) how VC affected the clinical decision-making of general practitioners (GPs). Methods A scoping review was conducted in accordance with the methodology of Joanna Briggs Institute. Review questions were formulated to match each focus area. A three-step search strategy was employed to search scientific and gray literature sources. MEDLINE, Embase, Scopus, OpenGrey, Google Scholar, and ClinicalTrials.gov were searched from 2010 to March 11th, 2021, and the search was re-run on August 18th, 2021. The extracted data were deductively coded into pre-defined main themes, whereas subthemes were inductively synthesized. The data within each subtheme were analysed through descriptive content analysis and presented in a narrative synthesis. Results Overall, 13 studies were included after screening 3,624 studies. Most patients were satisfied with VCs. VCs were most suitable for simpler issues, often shorter than face-to-face consultations, and were more likely to be used by younger patients. GPs enjoyed the flexibility and shorter duration of VCs; however, they felt an unsatisfactory deterioration in the GP-patient relationship. Despite the loss of clinical examination, diagnostic assessment was mostly successful, with little fear of missing serious illness. Prior clinical experience and a preexisting relationship with the patient were important factors for successful assessment via VC. Conclusions Both GPs and patients can be satisfied with VC in general practice in specific contexts, and adequate clinical decision-making is possible. However, disadvantages such as a diminishing GP-patient relationship have been highlighted, and the use of VC in non-pandemic settings is limited. The role of VC in the future of general practice remains unclear, and further research is needed on the long-term adoption of VC in general practice.